2021
DOI: 10.1080/14756366.2021.1900165
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-catalysed A-ring C–H activations and C(sp2)–C(sp2) couplings in the 13α-oestrone series and in vitro evaluation of antiproliferative properties

Abstract: Facile syntheses of 3-O-carbamoyl, -sulfamoyl, or -pivaloyl derivatives of 13a-oestrone and its 17-deoxy counterpart have been carried out. Microwave-induced, Ni-catalysed Suzuki-Miyaura couplings of the newly synthesised phenol esters with phenylboronic acid afforded 3-deoxy-3-phenyl-13a-oestrone derivatives. The carbamate and pivalate esters proved to be suitable for regioselective arylations. 2-(4-Substituted) phenyl derivatives were synthesised via Pd-catalysed, microwave-assisted C-H activation reactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The tested steroidal sulfamates (13AES1-3, Figure 1 ) were synthesized as described previously in detail [ 28 ]. For all in vitro experiments, 10 µM stock solutions of the test compounds were prepared with dimethyl sulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tested steroidal sulfamates (13AES1-3, Figure 1 ) were synthesized as described previously in detail [ 28 ]. For all in vitro experiments, 10 µM stock solutions of the test compounds were prepared with dimethyl sulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…The antiproliferative properties of the test compounds were determined on a panel of human gynecological cancer cell lines and were reported previously [ 28 ]. These previous results were now completed with assays on cells from breast (T47-D) and cervical (C33A) cancer using the same protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The group of 13α-estrone derivatives proved to be promising concerning their enzyme inhibitory and/or antiproliferative properties. However, their biological activity greatly depends on their structure [ 33 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. We have observed that the substitution pattern of ring A influences bioactivity markedly.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, triazole derivative 11b might be considered as an MSA agent with remarkable tumor selectivity concerning the cell lines investigated. More recently we have shown that 3-deoxy-3-phenyl-13α-estra-1,3,5(10)-triene ( 12 ) displays weak antiproliferative action [ 47 ]. This observation suggests that direct phenylation at C-3 by the simultaneous removal of the hydroxy group is detrimental regarding the antiproliferative action.…”
Section: Introductionmentioning
confidence: 99%